(untitled) (International Current Pharmaceutical Journal, 2013)
Pupalia lappacea Juss (Family: Amaranthaceae) is claimed to be useful in treatment of bone fracture, wounds, boils, cough, toothache, fever and malaria. The study was aimed to evaluate the 80% aqueous ethanolic extract of aerial parts of P. lappacea for antinociceptive and antipyretic activities to verify the traditional claim. The extract was orally administered at doses of 200, 400 and 600 mg/kg. The extract has significantly (P<0.01) reduced the nociception induced by acetic acid. The effect produced was in dose dependent manner. The antinociceptive effect was not reversed by pretreatment with naloxone in acetic acid induced writhing test. In hot plate method, the extract has significantly increased the latency time of jump. The naloxone has partially antagonised the antinociception of extract in hot plate test indicating P. lappacea has morphinomimetic properties. In the study of the CNS-depressant effects, the extract was found to produce significant reduction in head pokes and locomotion in mice by using hole board and locomotor activity test respectively. The extract has significantly reduced the rectal temperature in yeast induced pyrexia in rats at 600 mg/kg. The activity produced by extract was in dose dependent manner. Phytochemical investigation of ethanolic extract of P. lappacea revealed the presence of steroids and/or triterpenoids, flavonoids and phenolic compounds which may be responsible for antinociceptive and antipyretic activity of P. lappacea. DOI: http://dx.doi.org/10.3329/icpj.v2i2.13193 International Current Pharmaceutical Journal 2013, 2(2): 23-28